Knowledge management practices in micro and small enterprises in Sergipe, Brazil (Gestão & Regionalidade, 2016)
This study sought to identify the knowledge management practices which are adopted by micro and small firms in Sergipe, Brazil. Thus, an exploratory and descriptive qualitative study involving five projects installed in the clothing pole in Itabaianinha, Sergipe, was performed. The research method chosen for developing this work was multiple case study. Data were collected through the interviews, and the interviews were recorded, transcribed and weighted by the technique of content analysis. Results indicated that informal conversation with customers, representatives, suppliers and competitors, meetings with entrepreneurs, participation in courses and training, and also monitoring the market are the main knowledge management practices used by micro and small firms who attended the study. Moreover, it was observed that these practices help the management, creation, and dissemination of existing knowledge in the organization record, contributing to more sustainable management and value creation.